2015
DOI: 10.1038/ncb3110
|View full text |Cite
|
Sign up to set email alerts
|

Reduced adenosine-to-inosine miR-455-5p editing promotes melanoma growth and metastasis

Abstract: Although recent studies have shown that adenosine-to-inosine (A-to-I) RNA editing occurs in microRNAs, its effects on tumor growth and metastasis are not well understood. We present evidence of CREB-mediated low expression of ADAR1 in metastatic melanoma cell lines and tumor specimens. Re-expression of ADAR1 resulted in the suppression of melanoma growth and metastasis in vivo. Consequently, we identified 3 miRs undergoing A-to-I editing in the low-metastatic melanoma but not in highly metastatic cell lines. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
203
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(218 citation statements)
references
References 39 publications
9
203
0
Order By: Relevance
“…These effects are mediated by the ability of the edited miRNA to target AMFR combined with an inability to inhibit the original target RAP2A (Choudhury et al 2012). In melanoma, edited miR-455 has been proposed to suppress tumor growth and metastasis by upregulating tumor suppressor CPEB1 (Shoshan et al 2015).…”
mentioning
confidence: 99%
“…These effects are mediated by the ability of the edited miRNA to target AMFR combined with an inability to inhibit the original target RAP2A (Choudhury et al 2012). In melanoma, edited miR-455 has been proposed to suppress tumor growth and metastasis by upregulating tumor suppressor CPEB1 (Shoshan et al 2015).…”
mentioning
confidence: 99%
“…Liu et al (36) identified that miR-455-5p was associated with anaplastic lymphoma kinase expression. Shoshan et al (37) confirmed that miR-455-5p contributes to melanoma growth and metastasis through the downregulation of the tumor-suppressor gene cytoplasmic polyadenylation element binding protein 1. However, the exact role with respect to influencing cell proliferation and apoptosis, and the regulatory mechanism of miR-455-5p in colon cancer remains unclear.…”
Section: Discussionmentioning
confidence: 88%
“…of Pages 11 in metastatic melanoma cell lines was detected compared to primary tumors or normal melanocytes [69]. A recent paper also demonstrated that ADAR1 downregulation could be regulated by cAMP response element-binding protein (CREB) in metastatic melanoma [70]. In this cellular context, reduced levels of ADAR1 promoted tumor growth and cell proliferation, accompanied by a metastatic phenotype.…”
Section: Reviewmentioning
confidence: 93%
“…RNA editing-independent changes in miRNA expression may occur as a result of direct binding of ADAR1 to pri-miRNA or regulation of the miRNA processing machinery by ADAR1 [69]. Alternatively, RNA editing of three miRNAs, including miR-455-5p, has been reported [70]. Editing events resulted in changes in miRNA processing as well as in miR-455 targeting.…”
Section: Reviewmentioning
confidence: 97%